Analysis of Student Errors in Solving Math Problems for Class XII of Nursing Assistant at St. Thomas Maumere Vocational High School - Diah, Mohamad Nur; Dhema, Magdalena; Ete, Agustinus Angelaus (EduMatika: Jurnal MIPA, 2023)
This study analyzes students' mistakes in doing math problems on function limit material. This research was conducted at SMK Santo Thomas Maumere in semester 2 of the 2021/2022 academic year. This type of research is qualitative research. The subjects of the study were 3 students drawn from 26 students of class XII Nursing Assistants. The results of this study show that the types of mistakes made by students are fact, conceptual, principle, and procedural errors based on the classification of fundamental errors of mathematical objects. The factual error made by students is that students are mistaken in writing down the left limit and proper limit symbols. The misconception is that students do not understand the rules of the limit of a function. The principal error made by students is mistaken in describing a process. Finally, the procedural mistake made by the student is a mistake in writing. The factors that cause students to make mistakes in solving the function limit problem are that students do not know the left limit and proper limit symbols, students do not understand the concept of function limits, and prerequisite knowledge related to function limits owned by students is still minimal, students are not careful in solving function limit questions, and students still feel embarrassed if they ask teachers or colleagues regarding limit material that has not been understood